2021
DOI: 10.31083/j.ejgo4205144
|View full text |Cite
|
Sign up to set email alerts
|

Icariin induces apoptosis in breast cancer MCF-7 cells by regulating the MELK mediated PI3K/AKT signaling pathway

Abstract: To investigate the mechanism of icariin in promoting apoptosis of breast cancer cells by regulating the Phosphatidylinositol kinase (PI3K) PI3K/AKT signaling pathway mediated by Maternal embryonic leucine zipper kinase (MELK). Methods: Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and Western blotting were used to detect the expression of MELK. small interfering RNA (siRNA)-MELK cell transfection technology was used to detect the correlation between MELK and PI3K/AKT. Different icariin concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…40 Molecular mechanisms, such as apoptosis, oxidative stress, and ferroptosis, have been revealed to participate in the progression of a variety of diseases. [25][26][27][28][29][30] In sepsisinduced AKI, Huang et al demonstrated that suppressing pannexin-1 inhibited cell apoptosis, which could contribute cells. Furthermore, the application of NAC reversed the effects of CHAC1 on the apoptosis and ferroptosis of LPSinduced HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…40 Molecular mechanisms, such as apoptosis, oxidative stress, and ferroptosis, have been revealed to participate in the progression of a variety of diseases. [25][26][27][28][29][30] In sepsisinduced AKI, Huang et al demonstrated that suppressing pannexin-1 inhibited cell apoptosis, which could contribute cells. Furthermore, the application of NAC reversed the effects of CHAC1 on the apoptosis and ferroptosis of LPSinduced HK-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the abovementioned active ingredients, a variety of compounds with relatively high contents, which were identified by HPLC-MS/MS but not found to be enriched by network pharmacology analysis, exhibit antitumor effects. Icariin induces breast cancer cell apoptosis through the PI3K/AKT and SIRT6/NF-κB signalling pathways [ 23 , 24 ]. Icariin also induces apoptosis in tamoxifen-resistant breast cancer cells, suggesting that it may be used as an alternative treatment in cases with chemotherapeutic resistance [ 25 ].…”
Section: Discussionmentioning
confidence: 99%